1995
DOI: 10.1128/aac.39.2.545
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside dosing weight correction factors for patients of various body sizes

Abstract: Prior investigations have suggested the use of a dosing weight correction factor of ideal body weight (IBW) plus 40% excess body weight (EBW, where EBW ‫؍‬ total body weight [TBW] ؊ IBW) to determine the weight to use for aminoglycoside dosing in morbidly obese (TBW/IBW ratio, >2) patients. Little data are available to provide dosing information for underweight or moderately obese patients. We investigated aminoglycoside pharmacokinetics in 1,708 patients receiving gentamicin and tobramycin. Patients were stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 19 publications
0
60
1
Order By: Relevance
“…12 ± 16 Despite considerable variability among the various study populations, consensus dosing weight correction factors (DWCF) for aminoglycosides of 40% of excess body weight (EBW, EBW TBW-IBW) IBW are accepted by most clinicians. 12 Similar DWCF have been proposed for cipro¯oxacin. Allard et al measured cipro¯oxacin plasma concentrations after a dose of 400 mg in obese and normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…12 ± 16 Despite considerable variability among the various study populations, consensus dosing weight correction factors (DWCF) for aminoglycosides of 40% of excess body weight (EBW, EBW TBW-IBW) IBW are accepted by most clinicians. 12 Similar DWCF have been proposed for cipro¯oxacin. Allard et al measured cipro¯oxacin plasma concentrations after a dose of 400 mg in obese and normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Ventilator volume settings calculated using actual weight, particularly in obese patients, can result in excess ventilatory volumes, barotrauma, and hemody-namic compromise (1). Although most medications are dosed using actual, true body weight, some medications are best dosed using IBW, or a combination of IBW and actual body weight, particularly in obese patients (2)(3)(4). Although drug dosing and ventilator volume settings initiated in the ED are based on preliminary estimates and later adjusted based on the patient's response, the goal should always be to initiate drug dosing and ventilatory settings as close as possible to the patient's physiological requirements.…”
Section: Introductionmentioning
confidence: 99%
“…A validation set (102 patients) then compared the accuracy of IBW using true height calculated from the regression formula vs. IBW using gold-standard true height. Regression formula for men tibial length-IBW (kg) ‫؍‬ 25.83 ؉ 1.11 ؋ tibial length; for women tibial length-IBW ‫؍‬ 7.90 ؉ 1.20 ؋ tibial length; R 2 …”
mentioning
confidence: 99%
“…It has been suggested that loading doses of aminoglycosides be increased by a factor of 1 . 1 in underweight patients (74) . Drug clearance is also reduced in PCM for chloramphenicol, penicillin, quinine and isoniazid (51,53,(75)(76)(77)(78) .…”
Section: Antimicrobial Examplesmentioning
confidence: 99%
“…The mg/kg dosing of these drugs should then be based on an Adj-BW using a correction factor of 0 . 4 to represent the proportion of the excess body weight into which the aminoglycosides distribute (74,81) . There is very little data on the antifungal agents, but dosing based on BWt has been suggested for amphotericin as both Vd and clearance may be increased in obesity (82)(83)(84) .…”
Section: Antimicrobial Examplesmentioning
confidence: 99%